Iron deficiency in plants: an insight from proteomic approaches - López-Millán, Ana-Flor; Grusak, Michael A.; Abadia, Anunciación; Abadía, Javier (Frontiers in Plant Science, 2013)
Iron (Fe) deficiency chlorosis is a major nutritional disorder for crops growing in calcareous soils, and causes decreases in vegetative growth as well as marked yield and quality losses. With the advances in mass spectrometry techniques, a substantial body of knowledge has arisen on the changes in the protein profiles of different plant parts and compartments as a result of Fe deficiency. Changes in the protein profile of thylakoids from several species have been investigated using gel-based two-dimensional electrophoresis approaches, and the same techniques have been used to investigate changes in the root proteome profiles of tomato (Solanum lycopersicum), sugar beet (Beta vulgaris), cucumber (Cucumis sativus), Medicago truncatula and a Prunus rootstock. High throughput proteomic studies have also been published using Fe-deficient Arabidopsis thaliana roots and thylakoids. This review summarizes the major conclusions derived from these “-omic” approaches with respect to metabolic changes occurring with Fe deficiency, and highlights future research directions in this field. A better understanding of the mechanisms involved in root Fe homeostasis from a holistic point of view may strengthen our ability to enhance Fe-deficiency tolerance responses in plants of agronomic interest.